1992
DOI: 10.1111/j.1532-5415.1992.tb02132.x
|View full text |Cite
|
Sign up to set email alerts
|

Mild Vitamin D Deficiency and Secondary Hyperparathyroidism in Nursing Home Patients Receiving Adequate Dietary Vitamin D

Abstract: Despite apparently adequate calories, calcium, and vitamin D intake, hypovitaminosis D with compensatory PTH elevations occurs, regardless of season, in the nursing home population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
30
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 26 publications
3
30
1
Order By: Relevance
“…Since elderly people are much more prone to fracture, it is possible that the AI for vitamin D in the elderly in Japan would be higher. Institutionalized elderly have been our special concern, since they are at even higher risk of fracture ( 7 -9 ) and have been reported to have a high prevalence of vitamin D deficiency or insufficiency (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Since elderly people are much more prone to fracture, it is possible that the AI for vitamin D in the elderly in Japan would be higher. Institutionalized elderly have been our special concern, since they are at even higher risk of fracture ( 7 -9 ) and have been reported to have a high prevalence of vitamin D deficiency or insufficiency (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…Certain risk factors for vitamin D deficiency have been identified such as low sunshine exposure, advanced age, obesity, skin pigmentation, and malabsorption [14,15]. For decades we have recognized a very high rate of vitamin D deficiency among nursing home residents in the U.S [4,12]. In recent years, the nursing home environment has become more regulated and there has been increasing pressure to individualize care plans for residents.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency has long been recognized asan undertreated, but important factor in the health and well-being of older adults, especially in a skilled nursing facility [1][2][3][4][5][6][7][8][9]. It can cause osteomalacia, exacerbate osteoporosis, secondary hypo-parathyroidism, and has been linked to falls and fractures in the nursing home [4,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McMurtry and colleagues found that most veterans living in nursing homes have vitamin D insufficiency (3). We sought to determine the prevalence of vitamin D insufficiency in ambulatory US war veterans seen at the Atlanta VA Medical Center.…”
mentioning
confidence: 99%